ANALISIS PENGARUH VARIASI BENTUK DAN VARIASI DIMENSI TERHADAP DAYA DUKUNG PONDASI TIANG PANCANG PADA GEDUNG KULIAH BERSAMA DAN LABORATORIUM FEB UPN â€œVETERANâ€ JAWA TIMUR - Mochammad Nouval Diva Ramadhan; Dian Purnamawati Solin; Made Dharma Astawa (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2022)
The foundation is the most important parts of the lower structure in a building work. This is because the foundation has a function as a bearer and load-bearing that is above it. Therefore, careful calculations are needed accompanied by a comparative analysis of methods to get an efficient type of foundation. In this study, a calculation analysis will be carried out using the conventional method, namely the Mayerhof, Luciano Decourt and Reese O'Neil method to analyze the bearing capacity of the pile with two types of pile shapes namely circle and square accompanied by differences in pile dimension data 300 mm, 400 mm, 500mm and 600 mm with reference to the comparison of the foundation carrying capacity data with the PDA (Pile Driving Analyzer) test. As well as knowing the settlement of the pile foundation of the Joint Lecture Building and Laboratory of the FEB UPN "Veteran" East Java using the PLAXIS version 8.2 aid program. from the results of the study obtained the value of the bearing capacity of the foundation, the smallest deflection and settlement as well as the comparison of the BCR (Bearing Capacity Ratio) value close to 1, the foundation with variations in the shape of a square cross section with dimensions of 300 x 300 mm is efficient and safe to use.